Thigh Ischemia-Reperfusion Model Does Not Accelerate Pulmonary VO2 Kinetics at High Intensity Cycling Exercise - Helal, Lucas; do Nascimento Salvador, Paulo Cesar; de Lucas, Ricardo Dantas; Guglielmo, Luiz Guilherme Antonacci (Frontiers in Physiology, 2019)
Abstract Background: This study aimed to investigate the effect of a priming ischemia-reperfusion (IR) model on kinetics of pulmonary oxygen uptake (VO2) and cardiopulmonary parameters at a high-intensity exercise. We focused in the VO2 kinetics as the primary outcome and secondary outcomes were HR and O2 pulse kinetics. We hypothesized that the IR model would accelerate VO2 and cardiopulmonary kinetics during the exercise. Methods: 10 sedentary men (25.7 ± 4.7 years; 79.3 ± 10.8 kg; 177 ± 5 cm; 44.5 ± 6.2 mL.kg-1.min-1) performed a maximal incremental ramp test and 4 constant load sessions at the midpoint between ventilatory threshold and VO2max in separate days: two without IR (CON) and two with IR (IR). IR model consisted of a thigh bi-lateral occlusion for 15 minutes at pressure of 250 mmHg, followed by 3 minutes off before exercise. Results: There were no significant differences for any VO2 kinetics parameters (VO2base 1.08 ± 0.08 vs. 1.12 ± 0.06 L.min-1; P=0.30; τ 50.1 ± 7.0 vs. 47.9 ± 6.4 s; P=0.47), as well as for HR (MRT180s 67.3 ± 6.0 vs. 71.3 ± 6.1 s; P=0.54) and O2 pulse kinetics (MRT180s 40.9 ± 3.9 vs. 48.2 ± 5.6 s; P=0.31) between IR and CON conditions, respectively. Conclusion: We concluded that priming IR model used in this study does not influence on VO2, HR and O2 pulse kinetics during high-intensity cycling exercise. Keywords: oxygen uptake kinetics; ischemia-reperfusion; cardiopulmonary test.